STUDENTS' PERSPECTIVES ON THE INTEGRATION OF DIGITAL TECHNOLOGY IN LANGUAGE LEARNING POST-COVID-19 - Mulyani, Aulia; Fauziah; Diana, Novita (English Education and Applied Linguistics Journal (EEAL Journal), 2024)
This study aimed to explore students' perspectives on integrating digital technology into language learning after the Covid-19 pandemic. The study used a qualitative research method and collected data through questionnaires and semi-structured interviews conducted on April 29, 2024, at Ulumul Quran Senior High School. Twenty students participated in the study. The closed-ended questionnaire was analyzed using a Likert scale, while the semi-structured interviews were analyzed using thematic analysis following Braun and Clarke's (2006) approach. The findings indicated that students positively viewed integrating digital technology in English learning. They found digital technology enjoyable, engaging, attractive, easy to use, and helpful in their learning process.